Antibacterial activity and phenolic profile of the methanolic extract from the aerial parts of Hyptis suaveolens (Lamiaceae) - Bonilla-Landa, Israel; Callejas-Linares, José María; Cortazar Murillo, Elvis Marian; Ramón Farías, Feliza; Guevara-Valencia, Marina; Monribot-Villanueva, Juan Luis; Guerrero-Analco, José Antonio (Instituto de Ecología, A.C., 2022)
Background and Aims: Hyptis suaveolens is a well-known plant in Latin America for its medicinal properties. Despite its diverse uses in traditional medicine, there are few reports concerning its chemical composition. In addition, the antimicrobial activity against human-pathogen bacteria is known, but there are few reports about its activity on phytopathogenic bacteria, specifically for those affecting important crops. In this context, the main aims of this work were to determinate the antibacterial activity of H. suaveolens leaves on phytopathogenic bacteria, and their phenolic profile, in order to contribute to the knowledge of the phytochemical composition and bioactivity of H. suaveolens for phytosanitary applications.Methods: The plant material was collected, and the aerial parts were dried, milled, and extracted with methanol. The crude extract was tested against two phytopathogenic bacterial strains (Chryseobacterium sp. and Pseudomonas sp.). Finally, phenolic compounds were identified and quantified using ultra-high performance liquid chromatography coupled with mass spectrometry. Key results: The crude extract of H. suaveolens exhibited a moderate antibacterial activity against Chryseobacterium sp., and 14 phenolic compounds were identified and quantified, highlighting rosmarinic acid, which showed the highest concentration followed by quercetin-3-glucoside and rutin. Six phenolic compounds were identified and quantified for the first time in H. suaveolens.Conclusions: In this work, the antibacterial activity of H. suaveolens leaves was demonstrated and it may correlate with the identification and quantification of 14 phenolic compounds, particularly with the presence of rosmarinic acid.